Effect of nitrogen levels and weed management on weed flora and yield of direct-seeded rice (Oryza sativa) in southern part of Punjab - SINGH, VICKY; SEPAT, SEEMA; SINGH, JASBIR; GAUTAM, ANAND; AULAKH, G S (The Indian Journal of Agricultural Sciences, 2023)
An experiment was conducted at Krishi Vigyan Kendra, Ferozepur, Punjab during rainy (kharif) seasons of 2018 and 2019 to study the effects of nitrogen levels and weed management in direct-seeded rice (Oryza sativa L.) (DSR). The results indicated that pendimethalin + bispyribac (W1) (5.25 and 2.95 m2) and oxadiargyl + bispyribac (W2) (6.05 and 3.95 m2) application reduced the density of narrow-leaved weeds (NLW) and broad-leaf weeds (BLW) followed by oxadiargyl + fenoxaprop (W3) (7.0 and 4.55 m2) during both the years. Application of W1 decreased the total weed biomass by 84–98.2%, respectively compared to weedy check (W5) (80.1 and 94.8 g/m2) in both years. Treatment W1 and W2 recorded at par values of grain and straw yield followed by W3. An increase (48.6–72.0%) in grain yield was registered with weed practices compared to weedy check in DSR. W1 and W2 significantly recorded higher N uptake in grain (61.45 and 60.85 kg/ha) and total (100.8 and 99.45 kg/ha) followed by W3 (53.85 and 90.35 kg/ha, respectively). The high infestation of BLW with W3 resulted in the lowest weed control efficiency (WCE) (46.2–53.9%) among the weed control practices. N at 120 and 150 kg/ha recorded the low density and biomass of NLW and BLW. Application of 120 and 150 kg N/ha enhanced the grain yield (4.89 and 5.25 t/ha) and net returns (55.1 and 60.5 × 103 ₹/ha) in both years. No N application recorded lowest N uptake in grain (87.71 kg/ha) and total (80.26 kg/ha) compared to 150 kg N/ha in both years. N levels at 120 and 150 kg/ha recorded higher values of water control efficiency (WCE). Based on the findings, it may be concluded that pendimethalin + bispyribac and oxadiargyl + bispyribac with N 120 kg/ha application can reduce weed flora diversity with higher grain yield of direct-seeded rice in Punjab.